Pengaruh Ekstrak Etanol Daging Buah Pala (Myristica Fragrans Houtt) Pada Histopatologi Jantung Tikus Wistar Hiperglikemik - Nur, Amran; Fiskia, Ermalyanti; Hi Yusuf, Muhammad Fakhrur Rajih; A. Disi, Muhammad Zulfian; Mursin, Nita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
The heart is an organ significantly impacted by diabetes mellitus problems, as elevated free radical generation and oxidative stress from hyperglycemia activate the apoptosis and necrosis pathways in cardiac myocytes. This study aimed to ascertain the histological characteristics of the cardiac tissue in rats subjected to hyperglycemia following the administration of ethanol extract from nutmeg fruit flesh (Myristica fragrans Houtt). This study employed rice as a diabetes inducer in 25 rats, categorized into 5 treatment groups: group 1 received Na-CMC, group 2 received metformin, group 3 received a dosage of 100 mg/KgBW, group 4 received a dosage of 200 mg/KgBW, and group 5 received a dosage of 300 mg/KgBW. The detected data included alterations in body weight, blood glucose levels, organ mass, and cardiac histology. The data were evaluated employing the One-Way ANOVA test at a 95% confidence level (p<0.05). The findings indicated that all groups treated with nutmeg fruit flesh ethanol extract exhibited a substantial enhancement in the histopathology of rat hearts compared to the negative control group 0,03 (p<0.05). The administration of nutmeg fruit flesh extract can ameliorate histopathological damage to the hearts of hyperglycemic rats at doses of 100 mg/KgBW, 200 mg/KgBW, and 300 mg/KgBW, indicating that nutmeg fruit flesh may serve as a cardioprotective drug in diabetic subjects.